In the moment social experiences and perceptions of children with social anxiety disorder: a qualitative study - Halldorsson, B; Waite, P; Harvey, K; Pearcey, S; Creswell, C (Wiley, 2022)
Objectives: Childhood social anxiety disorder (SAD) is a common and disabling condition. General forms of cognitive behavioural treatments have demonstrated poorer efficacy for childhood SAD when compared to other childhood anxiety disorders and further understanding of the psychological factors that contribute to the maintenance of childhood SAD is warranted. Examining the social experiences of children with SAD may help to identify relevant psychological factors and increase our understanding of what keeps childhood SAD going. Methods: The current study used reflexive thematic analysis to analyse the transcripts of interviews with 12 children aged 8–12 years with SAD who had been interviewed about their ‘in the moment’ social experiences during a social stress induction task. The interview topic guide included factors hypothesized to maintain SAD in adult cognitive models of the disorder. Results: The interviews revealed both variety and commonalities in the experiences and interpretations of social events in children with SAD, captured in three related main themes: (i) Discomfort being the centre of attention, (ii) (Lack of) awareness of cognitions and (iii) Managing social fears. Findings indicated likely developmental influences on which maintenance mechanisms apply at which point in time. Conclusions: There is variation in the psychological mechanisms that children with SAD endorse and developmental factors are likely to influence when specific mechanisms are relevant. We now need further studies that take a developmentally informed approach to understand the nature of the association between the factors identified in this study and social anxiety in childhood to inform the development of more effective interventions for childhood SAD.